Sustainable Alternatives for Chemical Waste Management in Testing and Calibration Laboratory - Ranti Wulandari; Zaenal Abidin; Yudi Setiawan; Putri Nur Angelina (Indonesian Journal of Environmental Management and Sustainability, 2026)
Laboratory waste represents a growing global concern due to its potential impacts on environmental quality, human health, and safety when improperly managed. At IPB University, laboratory activities generate up to 5 tons of wastewater per month, emphasizing the need for effective and sustainable waste management strategies. This study proposes a structured gap-to-roadmap framework for independent chemical waste management in testing and calibration laboratories. The framework integrates criteria-based gap analysis, a literature-derived waste minimization checklist, and phased implementation planning. Data were collected through semi-structured interviews and literature review and analyzed using a qualitative, criteria-based approach. The results indicate that the PPLH IPB Laboratory generates approximately 100–481 L of chemical waste annually. While several minimization practices have been implemented, key gaps remain in standard operating procedures, labeling systems, temporary storage, and recovery and recycling practices. The checklist analysis further identifies feasible strategies, including solvent recycling and inter-laboratory chemical exchange, with significant potential for waste reduction and improved resource efficiency. The proposed framework translates identified gaps into targeted actions and assigns them into short-, medium-, and long-term implementation phases. This approach provides a practical and replicable tool for laboratories seeking to transition toward independent, compliant, and environmentally sustainable waste management systems, particularly in resource-constrained settings.